Development and validation of the Heidelberg Form for emotion regulation strategies (HFERST): factor structure, reliability, and validity - Izadpanah, Shahrzad; Barnow, Sven; Neubauer, Andreas B.; Holl, Julia (Assessment, 2017)
The Heidelberg Form for Emotion Regulation Strategies (HFERST) was developed to complement previous emotion regulation (ER) questionnaires and addresses some of their limitations by measuring eight ER strategies. An initial item pool was developed in German following expert discussions and adaptation of the items from existing ER scales. Following a stepwise selection based on the experts’ judgments, 32 items with the best content validity were chosen. Results of an exploratory factor analysis in Study 1 (N = 399) and two confirmatory factor analyses in Studies 2 (N = 715) and 3 (N = 408) supported the eight-factor structure of the HFERST and provided evidence for its internal consistency, construct and criterion validity, and clinical utility. Study 4 supported a 2-week stability of the HFERST and Study 5 showed that, following an ER intervention, the HFERST captured a reduction in dysfunctional and an improvement in functional ER strategies, which again supports the clinical utility of the HFERST.
Epub ahead of print
Gesehen am 09.08.2017